Analysis of Green Accounting, Carbon Emission Disclosure, and Corporate Social Responsibility on Firm Value with Profitability as a Moderating Variable in the Basic Materials Sector Listed on the Indonesia Stock Exchange - Dewi Kirowati; Abdul Halik; Siti Mujanah (Assets: Jurnal Akuntansi dan Pendidikan, 2026)
This study examines the effect of sustainability-related disclosures on firm value, focusing on carbon emission disclosure, corporate social responsibility (CSR), and green accounting, with profitability as a moderating variable (Nguyen P. A., 2023). The research is motivated by increasing regulatory and stakeholder pressure on firms to enhance transparency regarding environmental and social impacts (Kouloukoui D. S., 2022)). The sample consists of energy and basic materials companies listed on the Indonesia Stock Exchange during the 2022–2024 period, selected using purposive sampling (Hair, 2022). Panel data regression analysis is employed, and model selection tests indicate that the Random Effect Model is the most appropriate estimation approach (Baltagi, 2021). The results show that carbon emission disclosure and green accounting do not significantly affect firm value, while CSR has a significant negative effect, and profitability does not moderate these relationships (Ali, 2021). These findings suggest that sustainability disclosures have not yet become value-relevant information for investors in the Indonesian market (Dissanayake D. T., 2021).